First Report of Protective Activity of Paronychia argentea Extract against Tobacco Mosaic Virus Infection - Ahmed Abdelkhalek; Abdulaziz A. Al-Askar; Maha M. Alsubaie; Said I. Behiry (Plants, 2021)
The widespread use of chemical control agents and pesticides for plant-pathogen control has caused many human health and environmental issues. Plant extracts and biocontrol agents have robust antimicrobial activity against different plant pathogens. However, their antiviral activities are still being investigated. In the present study, the methanol extract of Paronychia argentea was characterized and evaluated for its protective activity against the tobacco mosaic virus (TMV) infection in tomato plants under greenhouse conditions at 21 days post-inoculation. The results showed that the foliar application of P. argentea extract (10 µg/mL) enhanced tomato plant growth, resulting in significant increases in shoot and root parameters and total chlorophyll contents. Moreover, a significant reduction in TMV accumulation level in P. argentea-treated plants of 77.88% compared to non-treated plants was reported. Furthermore, induction of systemic resistance with significant elevation in production of antioxidant enzymes (PPO, CAT, and SOD) and transcriptional levels of the pathogenesis-related proteins (PR-1 and PR-7) and polyphenolic genes (CHS and HQT) were also observed. Out of 16 detected compounds, HPLC analysis revealed that the most abundant polyphenolic compounds found in P. argentea extract were gallic acid (5.36 µg/mL), kaempferol (7.39 µg/mL), quercetin (7.44 µg/mL), ellagic acid (7.89 µg/mL), myricetin (8.36 µg/mL), and ferulic acid (8.69 µg/mL). The findings suggest that the use of P. argentea extract as an effective and safe source for the production of bioactive compounds may offer a solution for a promising approach for the management of plant viral infections. To the best of our knowledge, this is the first report of the protective activity of P. argentea extract against plant viral diseases.